Daily field checking list by Walter Rosene, April 30, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 30, 1932. This checklist was used by Walter Rosene to record birds sighted around Adix Ponds and North Bridge with Bob Walker between 6:00 and 9:00. Plustek--flatbed